Synthesis, Crystal Structure and Water Vapor Adsorption Properties of a Porous Supramolecular Architecture - Rui Qiao; Zi-You Zhang; Mei-An Zhu (Crystals, 2017)
A new complex, [Cu4(HL)4(H2O)14] (1, H3L·HCl = 5-((4-carboxypiperidin-1-yl)methyl)isophthalic acid hydrochloride), has been prepared and characterized by single-crystal X-ray diffraction, elemental analysis, IR spectroscopy and powder X-ray diffraction (PXRD). The result of the X-ray diffraction analysis reveals that the complex crystallizes in monoclinic, space group C2/c and three unique Cu(II) atoms that are connected by partially deprotonated HL2− anion to form a cyclic structure. The rich hydrogen bonding and π-π non-covalent packing interactions extend cyclic units into a three-dimensional (3D) supramolecular polymer. Moreover, the thermogravimetric (TG) analysis and water vapor adsorption property of 1 were also discussed.